Application of sensor technology for energy consumption analysis; a case study in a smart office building - Tee, Boon Tuan; Lim, S.C.J.; Siew, P.W.; Lee, M.F. (2023)
Understanding the energy consumption trends of a building is essential for effective energy management. The energy audit (EA) process is critical in attaining this insight since it quantifies energy consumption and its numerous facets. This paper investigates the incorporation of sensor technology into the energy audit process, focusing on a specific case study involving a building equipped with the KNX building automation system (BAS) as its fundamental energy management technology. The case study shows the practical implementation of sensors in gathering valuable data for energy research. The data collected not only aids in understanding energy usage patterns, but also sets the groundwork for the construction of an intelligent building energy management system. This study highlights the potential of sensor technology to transform the way we conduct energy audits and promote the shift to smarter, more efficient building management.